When Are Depolarizing GABAergic Responses Excitatory? - Kilb, Werner (Frontiers in Molecular Neuroscience, 2021)
The membrane responses upon activation of GABA(A) receptors critically depend on the intracellular Cl− concentration ([Cl−]i), which is maintained by a set of transmembrane transporters for Cl−. During neuronal development, but also under several pathophysiological conditions, the prevailing expression of the Cl− loader NKCC1 and the low expression of the Cl− extruder KCC2 causes elevated [Cl−]i, which result in depolarizing GABAergic membrane responses. However, depolarizing GABAergic responses are not necessarily excitatory, as GABA(A) receptors also reduces the input resistance of neurons and thereby shunt excitatory inputs. To summarize our knowledge on the effect of depolarizing GABA responses on neuronal excitability, this review discusses theoretical considerations and experimental studies illustrating the relation between GABA conductances, GABA reversal potential and neuronal excitability. In addition, evidences for the complex spatiotemporal interaction between depolarizing GABAergic and glutamatergic inputs are described. Moreover, mechanisms that influence [Cl−]i beyond the expression of Cl− transporters are presented. And finally, several in-vitro and in-vivo studies that directly investigated whether GABA mediates excitation or inhibition during early developmental stages are summarized. In summary, these theoretical considerations and experimental evidences suggest that GABA can act as inhibitory neurotransmitter even under conditions that maintain substantial depolarizing membrane responses.